Some paranormed Euler sequence spaces of difference sequences of order m - Karakaya, Vatan; Savas, Ekrem; Polat, Harun (VERSITA, 2013)
The main purpose of this work is to extend the sequence spaces which are defined in [KARAKAYA, V.-POLAT, H.: Some new paranormed sequence spaces defined by Euler and difference operators, Acta Sci. Math. (Szeged) 76 (2010), 87-100] and [POLAT, H.-BASAR, F.: Some Euler spaces of difference sequences of order m, Acta Math. Sci. Ser. B Engl. Ed. 27 (2007), 254-266] by using difference operator of order m, and to give their alpha, beta and gamma duals. Furthermore, we characterize some classes of the related matrix transformations.
Keywords: paranormed sequence space; matrix mapping; Kothe-Toeplitz duals; Euler transformation and difference sequence spaces of order m; INCLUDE; L(P); Mathematics